The influence of a modified blood supply on craniofacial growth in the rabbit. 3. Skull and lower jaw: General development in size - Brehmer, Axel; Beleites, Bernhard (Anatomischer Anzeiger, 1989)
This report deals with the growth of the skull and lower jaw after unilateral ligation on the common carotid artery in juvenile rabbits. No differences that could be attributed to the operation were found between the animals with ligated carotids and the control animals.